Studies on conception rates, calving rates and calf mortality rates in beef and dairy herds at Bunda College farm - Munthali, B.C. (1982)
The reproductive performance of beef and dairy herds at Bunda were investigated over a period of 3 years. Data on conception rate, calving, calf mortality rates, and comparative performances between Malawi Zebu, Brahman, Brahman x zebu and other crosses included.